Pengaruh Free Cash Flow, Kualitas Audit, dan Pertumbuhan Laba Terhadap Manajemen Laba Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Fachri Pasha; Khomsiyah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this research is to determine whether there is an effect of free cash flow, audit quality, and earnings growth on earnings management with company size as a moderating variable. The data in this study uses discretionary accruals calculated using the modified jones model. This study uses consumer cyclicals and consumer non-cyclicals companies listed on the Indonesia Stock Exchange for the period 2020 to 2022 and uses purposive sampling method. The data analysis method used in this study is multiple linear regression.The sample in this study amounted to 192 data and minus 1 data due to outliers, so that in this study the data used amounted to 191. The results of this study concluded that free cash flow and earnings growth have a negative effect on earnings management, while audit quality has a positive effect on earnings management. In addition, company size does not weaken and strengthen the effect of free cash flow and earnings growth on earnings management, but company size can weaken audit quality on earnings management.